The use of medical apps amongst doctors working in the Department of Paediatrics and child health of the University of the Witwatersrand, in Johannesburg South Africa - Mahmood, Shahid (My University, 2020)
Background: Use of medical apps by healthcare professionals is common in their day to day practice. Doctors use medical apps for gathering reference information, patient management, clinical decision making, communication, counselling, data and information management, medical education and training as well. The rapid proliferation of medical apps raises concerns about quality, efficacy, security, safety and reliability of applying these apps in clinical practice. There should be regulatory bodies with oversight on the medical apps. Aim: The purpose of this study was to look at the number of doctors using medical apps, types of medical apps being used, the frequency of usage, and their trends while choosing these apps, in the Department of Paediatrics in the School of Medicine at the University of the Witwatersrand, Johannesburg. To also determine their knowledge regarding any regulations around medical app development. Method: A cross-sectional study design using a questionnaire was used to collect data in this study. This was done via an online survey. The questionnaire was sent to medical practitioners in selected hospitals. Results: A total of 150 medical doctors participated in this study and 73.2% reported using clinical apps several times a day. Registrars, consultants, interns and medical officers reported using the mobile app 81.7%, 54%, 85.7% and 84.2% respectively several times a day. Reference tools (81.7%), diagnostic tools (58.17%) and clinical decision-making support tools (43.79%) were the three most common medical apps used in clinical practice. Peer recommendation (75.8%), app credibility (66%), functionality (65.4%), usability (64.7%) and used or recommended by a senior (60.1) are the common criteria used in evaluating a potential app for use in clinical practice. v Updated regularly (73.2%), scientifically evaluated (71.2%), peer-reviewed (64.1%) and approved by a regulatory body (59.5%) are the most common requirements identified in recognizing a high-quality application. Conclusion: Medical apps are being increasingly used by medical doctors of all ranks, supporting them in their clinical decision making, improving patient management and making better communication amongst the health professionals at different levels. However, they need more training and support regarding selection, usability and dealing with potential hazards. Improved awareness of the regulations surrounding medical apps amongst doctors is required
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine in Paediatrics to the Faculty of Health Sciences, School of Medicine, University of the Witwatersrand, Johannesburg, 2020